2021
DOI: 10.3390/v13030421
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in the Domain II, 3′ Untranslated Region of Human and Mosquito Derived Dengue Virus Strains in Sri Lanka

Abstract: Genetic variations in dengue virus (DENV) play a distinct role in epidemic emergence. The DENV 3′ UTR has become a recent interest in research. The objective of the study was to examine the genetic variation in the domain II, 3′ UTR region of human and mosquito-derived DENV. DENV-infected human sera were orally infected to laboratory reared Aedes aegypti mosquitoes. The domain II, 3′ UTR of each human- and mosquito-derived sample was amplified. The nucleotide sequence variation, phylogenetic and secondary stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The possibility of increased transmission and epidemic situations has been reported if any minor genetic changes occur in flavivirus RNA [ 26 ]. Furthermore, it has been reported that genetic variation in 3′UTR contributes to epidemic emergence [ 27 ]. Several reports have suggested that the insertions/deletions in 3′UTR have recently contributed to disease pathogenicity [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of increased transmission and epidemic situations has been reported if any minor genetic changes occur in flavivirus RNA [ 26 ]. Furthermore, it has been reported that genetic variation in 3′UTR contributes to epidemic emergence [ 27 ]. Several reports have suggested that the insertions/deletions in 3′UTR have recently contributed to disease pathogenicity [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…This basic structure is also observed in JEV, WNV, MVE and KUN. The DB2 structure is absent in YFV and ZIKV, and both DB1 and DB2 are absent in the TBE genome; however, the formation of pseudoknots is apparently a common feature observed in all MBFV ( Olsthoorn and Bol, 2001 ; Funk et al., 2010 ; Kasprzak and Shapiro, 2014 ; de Borba et al., 2019 ; Dayananda et al., 2021 ). These structures are relevant for replication efficiency, since mutations that disrupt them result in the generation of DENV-3 with an attenuated phenotype in SCID-Huh-7 mice, mosquitoes, and rhesus monkeys ( Blaney et al., 2008 ; de Borba et al., 2019 ) and a reduction in the replication efficiency of KUN ( Funk et al., 2010 ).…”
Section: Flavivirus 3’ Utrmentioning
confidence: 99%